Notificação sensível ao contexto: uma análise de aceitação - Marinho , Carlos S.S.; Junior, Messias; Viana, Windson (Anais Estendidos do Simpósio Brasileiro de Sistemas Multimídia e Web (WebMedia), 2016)
This research work investigates the design, development and evaluation of a context-aware notification system. We designed a mobile application called AvisaE. It implements theˆ concept of context-aware notification, i.e., a notification that is triggered when a pre-defined context is validated. The software enables the registration reminders, if the user is on a schedule and at a specif location then a notification warning is triggered. We interviewed ten users following the System Usability Scale model (SUS) to assess the acceptance of the proposed system, which was considered“good”by the evaluators. Sixty percent of respondents showed interest in using the system continously.